Comparison of shielding performance of Al/Mg impedance-graded-material-enhanced and aluminum Whipple shields. (April 2019) - Zhang, Pinliang; Gong, Zizheng; Tian, Dongbo; Song, Guangming; Wu, Qiang; Cao, Yan; Xu, Kunbo; Li, Ming
Highlights: The gradient material bumper shows some promise for the shielding performance of Whipple shields. This study investigated the main factors in performance improvement, except higher shock pressures and temperature rise in the projectiles caused by the high-acoustic-impedance coating of bumpers. In this study, a series of tests revealed the shielding performance of the Al/Mg shield, and the result suggests that the enhanced shield can make a sharp improvement in the protective capability compared with aluminum shields. There is reasonably compelling evidence that the shock wave property is largely responsible for fragmentation of the materials. Therefore, wave propagation in the projectile and bumper is discussed. Through experiments and theoretical analysis, some interesting phenomena and consistent conclusions were found. Abstract: The gradient material bumper shows promise to improve shielding performance of Whipple shields. The purpose of this study is to investigate the main factors in performance improvement. Comparison experiments have been performed on Al/Mg impedance-graded-material-enhanced and conventional aluminum Whipple shields using a two-stage light-gas gun at impact velocities of 3.5 and 6.5 km/s. They show that the shielding capability of Al/Mg shields is greater than that of conventional aluminum shields with the same bumper areal density. Hypervelocity impact characteristics, including debris clouds and damage patterns on the rear wall, have been studied, and consistent results have been achieved. To explore the reasons for the superior shielding capability of Al/Mg shields, some theoretical analysis and calculations were carried out. The results show that the projectiles receive equal shock pressures and temperature rise when impacting on Al/Mg and aluminum bumpers, which because the bumpers possessing the same acoustic-impedance surface materials. However, the Al/Mg bumper can breakup the projectile into smaller parts and spread the projectile fragments over a greater area, because the particular shock wave transfer is affected by shock impedance mismatch. In addition, the shock heating effect for the Al/Mg bumper plays an important role in contributing to kinetic energy attenuation and bumper material fracture, thereby causing a sharp increase in protective capability for spacecraft meteoroids/debris shielding. Finally, the ballistic limit curve of Al/Mg shields was preliminarily obtained.